âARITâ AUTOMATIC RICE TRANSPLANTER ALAT PENANAM PADI TENAGA SURYA BAGI PETANI GODEAN - Anandito, Akhsanto (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Rice is the staple food of Indonesia. However, dosmetic rice production can not be relied upon to meet the amount of national food needs. The demands of the nations consumption of rice per capita forcing Indonesia to import rice. In long term, it is feared Indonesian addicted to another country so that national food self-sufficiency can not be realized. Therefore, efforts should be made to increase domestic rice production. The application of technology tools and agricultural machinery is needed to develop agriculture in Indonesia. ARIT (Automatic Rice Transplanter) comes to be the answer. ARIT is a tool or a rice-planting machine designed with innovative technology. Agricultural productivity in Indonesia is less well with the majority of farmers who had been elderly and the limited number of rice planter labor, do not be a significant constraint again with this technology. ARIT making farmers work become more effective and efficient with higher productivity. Currently, the initial target is ARIT invention can help solve three fundamental problems being faced by our client, Kelompok Tani Makmur Cokrobedog which is in Godean, Yogyakarta. The majority of Godean farmers who had been elderly, the number of rice planter labor in Godean which is increasingly rare, and low rate of farmer regeneration can be solved through the application of ARIT in the client regions.Keywords: Rice, national food needs, agricultural productivity, rice transplanter